Evaluation of changes in oral drug absorption in preterm and term neonates for Biopharmaceutics Classification System (BCS) class I and II compounds. (30th October 2015) - Somani, Amit A.; Thelen, Kirstin; Zheng, Songmao; Trame, Mirjam N.; Coboeken, Katrin; Meyer, Michaela; Schnizler, Katrin; Ince, Ibrahim; Willmann, Stefan; Schmidt, Stephan
Abstract : Aims: Evidence suggests that the rate of oral drug absorption changes during early childhood. Yet, respective clinical implications are currently unclear, particularly for preterm neonates. The objective of this study was to evaluate changes in oral drug absorption after birth for different Biopharmaceutics Classification System (BCS) class I and II compounds to better understand respective implications for paediatric pharmacotherapy. Methods: Two paradigm compounds were selected for BCS class I (paracetamol (acetaminophen) and theophylline) and II (indomethacin and ibuprofen), respectively, based on the availability of clinical literature data following intravenous and oral dosing. A comparative population pharmacokinetic analysis was performed in a step‐wise manner innonmem ® 7.2 to characterize and predict changes in oral drug absorption after birth for paracetamol, theophylline and indomethacin. Results: A one compartment model with an age‐dependent maturation function for oral drug absorption was found appropriate to characterize the pharmacokinetics of paracetamol. Our findings indicate that the rate at which a drug is absorbed from the GI tract reaches adult levels within about 1 week after birth. The maturation function for paracetamol was found applicable to theophylline and indomethacin once solubility limitations were overcome via drug formulation. The influence of excipients on solubility and, hence, oral bioavailability was confirmed for ibuprofen, a second BCS class II compound. Conclusions: The findings of our study suggest that the processes underlying changes in oral drug absorption after birth are drug‐independent and that the maturation function identified for paracetamol may be generally applicable to other BCS class I and II compounds for characterizing drug absorption in preterm as well as term neonates.